Alginate foam-based three-dimensional culture to investigate drug sensitivity in primary leukaemia cells. Issue 141 (30th April 2018) - Karimpoor, Mahroo; Yebra-Fernandez, Eva; Parhizkar, Maryam; Orlu, Mine; Craig, Duncan; Khorashad, Jamshid S.; Edirisinghe, Mohan
Abstract : The development of assays for evaluating the sensitivity of leukaemia cells to anti-cancer agents is becoming an important aspect of personalized medicine. Conventional cell cultures lack the three-dimensional (3D) structure of the bone marrow (BM), the extracellular matrix and stromal components which are crucial for the growth and survival of leukaemia stem cells. To accurately predict the sensitivity of the leukaemia cells in an in vitro assay a culturing system containing the essential components of BM is required. In this study, we developed a porous calcium alginate foam-based scaffold to be used for 3D culture. The new 3D culture was shown to be cell compatible as it supported the proliferation of both normal haematopoietic and leukaemia cells. Our cell differential assay for myeloid markers showed that the porous foam-based 3D culture enhanced myeloid differentiation in both leukaemia and normal haematopoietic cells compared to two-dimensional culture. The foam-based scaffold reduced the sensitivity of the leukaemia cells to the tested antileukaemia agents in K562 and HL60 leukaemia cell line model and also primary myeloid leukaemia cells. This observation supports the application of calcium alginate foams as scaffold components of the 3D cultures for investigation of sensitivity to antileukaemia agents in primary myeloid cells.